PARTY BUILDING IN TAJIKISTAN - MULLOJANOV, Parviz (CENTRAL ASIA AND THE CAUCASUS, 2005)
Party building in a genuinely democratic society appears to be a rather simple affair: the people elect political parties, and the one that receives the majority of votes forms the government and determines the priorities of state policy until the next election. So, ideally, political parties are voluntary organizations which form a bridge between the people and the government, thus creating an efficient system along the lines of people-party government. In so doing, the parties that lose the election create the opposition with the confidence that the government system itself guarantees their right to engage in political activity. Real party building looks much more complicated, particularly in countries like the CIS states where democracy is incomplete or still developing. The former Soviet republics began from the same starting point, they all rejected the totalitarian Soviet-style system dominated by one party and a single ideology. But during the past fourteen years, each country of the Commonwealth has taken certain steps toward democracy. For example, whereas Turkmenistan and Belarus have simply made cosmetic changes to the old Soviet system of governance, in Ukraine and Georgia political parties are already capable of having a significant impact on the election results. But none of them have yet been able to make the transition to the above-mentioned formula of people-party-government. Across the board, the formation of parties and party building have ended up in the hands of the local elites—clan, regional, business circles, criminal, family, and so on. These elites are merely using political parties as a tool to gain or retain power. And this power is all the more coveted as the fight continues for deficit resources and a share in the divvying up of property. In this situation, the people are just as alienated from politics as they were in the Soviet system. Whereby the scarcer the resources, the more intense the struggle for power. It is customarily believed that political parties in Tajikistan are formed according to the territorial principle, and the interparty struggle is most often seen as a standoff among the regional elites. But regionalism did not become an indispensable part of our republic’s political life overnight. It is a rather complicated process that has been going on for more than one decade now.